Film “Gadis Kretek”; Dikalahkannya Perjuangan Perempuan dalam Masyarakat Patriarki - Aisya Tsaqifa Arumi; Eni Maryani; Subekti W. Priyadharma (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Gadis Kretek is a series exclusively aired on the subscription streaming platform, Netflix. It tells the story of a woman named Dasiyah who fights against patriarchal values that she feels are unfair to her as a woman. This study uses a qualitative method with narrative analysis through four elements in the film, namely plot, premise, characterization, and conflict. The results reveal that there are strong patriarchal values regarding women as shown through the plot, premise, characterization, and conflict in the Gadis Kretek series. The plot or storyline shows Dasiyah's dependence on men. The premise of this film assumes that women who fight against patriarchal values will experience defeat. Dasiyah, as a woman, has a strong character but is alone, surrounded by men with characters who silently support her, and a very patriarchal tobacco sauce chef. Dasiyah faces various conflicts both with her partner and with patriarchal figures who oppose her desire to become a sauce maker in the tobacco industry, making women victims in political conflicts that women do not understand. In the end, the Gadis Kretek series concludes with the bitterness of Dasiyah's life and the success of men using the tobacco sauce formula created by Dasiyah without her knowledge.